Budaya Birokrasi Dalam Mewujudkan Good Governance Di Sekretariat Daerah Provinsi Kalimantan Tengah - Oktipia Pengestika; Bulkani Bulkani; Novianto Eko Wibowo (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2020)
The purpose of this research is to know and describe the bureaucratic culture in realizing good governance in the regional secretariat of central Kalimantan province. As well as to develop the bureaucratic cultural strategy in the Regional secretariat of central Kalimantan province in realizing good governance. The study used a qualitative approach. The research data is derived from live observations, interviews, and collecting documents. The informant in this research is the official and staff in the regional secretariat which considered relevant and competent related in organizing the bureaucratic culture in the regional secretariat. The results showed that the government bureaucracy culture in the central Kalimantan provincial secretariat is still trapped into the mechanistic static bureaucratic culture, the pathological bureaucracy and cultural bureaucratic bureaucracies, so Great influence on bureaucracy performance in realizing Good Governance. Advice that can be given by researchers is the leader of bureaucracy organization to have a clear vision and mission and can be an example of good examples for his subordinates and has a strong commitment to realizing the bureaucratic culture needed Organization. By first diagnose the culture that there is written bureaucracy.